2017
DOI: 10.1016/j.acra.2017.05.014
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Low-intensity Vibration to Improve Bone Health in Patients with End-stage Renal Disease Is Highly Dependent on Compliance and Muscle Response

Abstract: Rational and Objectives Low intensity vibration (LIV) may represent a nondrug strategy to mitigate bone deficits in patients with end-stage renal disease. Materials and Methods Thirty end-stage renal patients on maintenance hemodialysis were randomized to stand for 20 minutes each day on either an active or placebo LIV device. Analysis at baseline and completion of 6-month intervention included magnetic resonance imaging (tibia and fibula stiffness; trabecular thickness, number, separation, bone volume fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Low intensity vibration in patients with chronic kidney disease increases strength parameters of the tibia due to changes in the trabecular compartment but not the cortex [4]. …”
mentioning
confidence: 99%
“…Low intensity vibration in patients with chronic kidney disease increases strength parameters of the tibia due to changes in the trabecular compartment but not the cortex [4]. …”
mentioning
confidence: 99%
“…The low level of physical activity among these patients, specifically the low level of moderate/vigorous physical activity, can even induce a decrease in BMD as a consequence of disuse, so the present results of the present study may be influenced by the fact that the women registered longer times of moderate/vigorous activity and lower values of BMD than did men. In fact, renal osteodystrophy is a multifactorial and pervasive disorder of bone and mineral metabolism that is present in individuals with CKD [38]. This disorder leads to a decrease in BMD and increases the risk of bone fracture [39].…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding the effects of WBV training in CKD patients are scarce. Recent pilot studies indicated that WBV training has the potential to attenuate bone deficits and improve physical function in this population ( Doyle et al, 2017 ; Rajapakse et al, 2017 ). Our results may be of great clinical importance in the treatment of people with CKD.…”
Section: Discussionmentioning
confidence: 99%